Heterogeneous dissociation process of truncated RNAs by oligomerized Vasa helicase - Kinoshita, Yoshimi; Murakami, Ryo; Muto, Nao; Kubo, Shintaroh; Iizuka, Ryo; Uemura, Sotaro (Communications biology, 2021)
RNA helicases are enzymes that generally unwind double-stranded RNA using ATP hydrolysis energy, mainly involved in RNA metabolism, transcription, translation, and mRNA splicing. While the helicase core is crucial for RNA unwinding activity, N- and C-terminal extensions of specific helicases may contain an intrinsically disordered region for electrostatic interaction, resulting in the formation of droplets in the cytoplasm. However, how the disordered region of the RNA helicase contributes to RNA unwinding and dissociation remains unclear. Here, we focused on Bombyx mori Vasa, which unwinds truncated target transposon RNAs from the piRNA-induced silencing complex piRISC. In this study, we used single-molecule techniques to visualise how Vasa dynamically interacts with piRISC and investigate how Vasa oligomerization is involved in the process of piRNA amplification, named the ping-pong pathway. We found that Vasa’s oligomerization is required during these processes in vitro and in vivo, and that Vasa triggers the dissociation of truncated RNA in heterogeneous pathways. Our single-molecule results suggest that oligomerized Vasa guides the timing of the process regulating overall dissociation efficiency. Kinoshita et al. use single molecule imaging to show that the N-terminal extension of BmVasa, a germ-specific DEAD box RNA helicase, is necessary for protein oligomerization and the dissociation of target RNA from the Siwi-piRISC complex. The authors conclude that oligomerized Vasa guides the timing of the regulation of overall dissociation efficiency.